Changes of protein composition and its relevance with textural properties during processing of fermented solid beef. Issue 6 (16th March 2017) - Zhou, Yajun; Ma, Yongqiang; Yao, Guangming; Li, Junxia; Wang, Shujie
Abstract: In this paper, fermented solid beef inoculated with two starter cultures ( Lactobacillus curvatus and Pediococcus pentosaceus ) in different inoculums concentration, fermentation time, and fermentation temperature was evaluated for change of protein composition (water‐soluble proteins, insoluble protein, and salt‐soluble proteins) and nonprotein nitrogen during fermentation and the relevance with textural properties was also investigated. The amount of water‐soluble and salt‐soluble proteins decreased while nonprotein and insoluble proteins increased as fermentation progressed. With the increase of inoculums concentration from 0.5% to 2.5%, the amount of water‐soluble and salt‐soluble proteins decreased from 23.8 to 19.6 mg/g and 51.2 to 33.5 mg/g, respectively, and the amount of nonprotein and insoluble proteins increased from 17.8 to 24.4 mg/g and 20.3 to 49.5 mg/g, respectively. During 0 to 32 hr of fermentation, the water‐soluble and salt‐soluble proteins decreased from 24.4 to16.0 mg/g and 54.0 to 22.0 mg/g, respectively, and the amount of nonprotein and insoluble proteins increased from 16.3 to 30.8 mg/g and 19.6 to 70.5 mg/g, respectively. With the fermentation temperature increased from 20°C to 40°C, the water‐soluble decreased from 34.6 to 21.8 mg/g; the amount of salt‐soluble proteins decreased from 60.0 to 21.2 mg/g; the nonprotein and insoluble proteins increased from 16.2 to 24.3 mg/g and 29.7 to 70.4 mg/g, respectively. From SDS‐PAGE analysis of water‐soluble and salt‐soluble proteins, solid beef protein tended to degrade to smaller protein, peptide, and amino acid with protease and peptidases enzymes, and partially form large polymers. Hardness, elasticity, gumminess, and chewiness were significantly negatively correlated with water‐soluble and salt‐soluble proteins, and were significantly positively correlated with insoluble proteins. The optimum inoculum population, fermentation time, and fermentation temperature were 2%, 32 hr, and 35°C, respectively. Practical applications: Our paper studied the effects of fermentation conditions including inoculums concentration, fermentation temperature, and fermentation time on the change of protein composition of fermented solid beef and nonprotein nitrogen. Meanwhile, explored the relationship between the protein composition and texture properties. Fermentation degrades proteins into smaller protein, peptides, and free amino acids. It is beneficial for absorption and good for health. And now the fermentation meat products become more and more popular. However, the quality of beef products is related to muscle proteins that the changes of protein molecules can be effectively affected the properties of products. Our preliminary observation provides a theoretical basis for further researches on quality evaluation of fermentation meat products, and hope to improve the quality of fermentation meat products.